Enhanced air-stability of Sn-based hybrid perovskites induced by dimethylammonium (DMA): synthesis, characterization, aging and hydrogen photogeneration of the MA1−xDMAxSnBr3 system. Issue 23 (22nd May 2019) - Pisanu, Ambra; Speltini, Andrea; Quadrelli, Paolo; Drera, Giovanni; Sangaletti, Luigi; Malavasi, Lorenzo
Abstract : A novel air-stable Sn-based hybrid perovskite system, MA1− x DMA x SnBr3, system is provided. Abstract : Polycrystalline powder samples of the novel MA1− x DMA x SnBr3 system have been synthesized and characterized concerning their structural and optical properties. The progressive alloying on the A-site occurs up to x = 0.60 and results in a linear blue-shift of the absorption edge with the DMA content. Mixed phase samples maintain the cubic crystal structure of parent MASnBr3 with a quasi-linear expansion of the cell volume as the DMA content increases. Aging test coupled with X-ray photoelectron spectroscopy indicates that DMASnBr3 is highly tolerant against air-exposure in terms of both crystal structure and optical properties thus representing a first example of highly-stable Sn(ii )-containing hybrid perovskite. In addition, thanks to such stability, proof-of-concept and demonstration of hydrogen photogeneration by DMASnBr3 is reported. Evidence of air-stabile Sn(ii )-containing perovskites represent a significant further step in the development of tin-containing photovoltaic devices.